A Comparative study of external dacryocystorhinostomy versus endonasal dacryocystorhinostomy (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Surgical treatment of dacryocystitis dates back to nearly 2000 years ago described as  creating an artificial passageway into the nose using hot cautery to puncture through the lacrimal bone.  Better understanding of lacrimal physiology and nasal and lacrimal anatomy through the centuries led to  development of a procedure that would resemble a modern external DCR surgery in the 18th century.  Intranasal approach operations had also been described in the 20th century. Advancements in methods of  DCR surgery have been procured in view of cosmesis, amount of bleeding, duration of surgery, and  outcome of the procedure. Aim/Objective: The aim of this study is to compare endonasal DCR and external DCR in the following  prospects: I) Bleeding Time II) Sac Patency III) Surgical Time IV) CosmesisMethods: This was a hospital based, interventional, prospective, non-randomized study of a total of 100  randomly selected patients of chronic dacryocystitis from OPD. 50 patients underwent external DCR and  50 patients underwent endonasal DCR. Young patients with good nasal space and without any nasal  abnormality were operated for endonasal DCR, and old patients or those with nasal abnormalities were  operated for external DCR. Preoperative assessment included an ENT evaluation, blood pressure, sac  syringing, and blood investigations. Surgery was performed and post-operative assessments were  conducted in the aspects of complications of surgery, intraoperative bleeding, surgical time and outcome  of surgery. Results: From a total of 100 patients, 59% were females of which 54% were operated by endonasal  DCR, with 30% of the population of total persons operated aging 60-70 years. There is more prevalence  of dacryocystitis in females and in old aged patients in this study due to more chances of lacrimal pump  failure in old age, and hormonal factors, smaller skull size and application on local cosmesis for females.  Punctum patency after 6 months comparing endonasal and external DCR surgery using chi square  formula proved a P value of 0.0008 which is highly significant showing that external DCR has  significantly higher success rate than endonasal DCR. In the aspect of complications, the study proved a  greater chance of recurrence of epiphora in external DCR, also the presence of a skin scar and wound dehiscence persists as a complication in external DCR due to the external skin incision which is not made  in endonasal DCR. Conclusion: DCR is the treatment of choice for nasolacrimal duct obstruction, and it can be performed  by external or endoscopic approach. Both approaches have minimal complications and comparable  surgical outcome, hence the choice of surgery should depend upon the patient’s preference, availability  of resources and surgeon’s expertise.
Keywords: Endonasal DCR; External DCR; Nasolacrimal duct obstruction; dacryocystitis; sac syringing